Role of Family Support Division (FSD) in helping single Muslim parents in Malaysia: an overview - Abdul Hak, Nora (2011)
In Malaysia, it is reported that in the year 2000 there were 128,810 single parent families, and the number has been increasing. Past research had found that single parent families and their children experienced more difficulties in the context of family life and well-being than two-parent families (Anjli Panalal K. Doshi, 2005). From the legal perspective, one of the problems of single parents is the difficulty of enforcement of the alimony order granted by the courts upon divorce. Recognizing this, the Government in 2008, decided to establish a new division known as the Family Support Division (FSD) under the Department of Shariah Judiciary of Malaysia. This division is to handle matters related to the enforcement of the maintenance orders issued by the Shariah courts against ex-husbands/fathers. Alimony advances will be made by the division to help the divorcees and their children whose ex-spouses or fathers failed to provide maintenance, or comply with the Shariah court’s order. In principle, this function is similar to that of the Child Support Agency (CSA) found in other countries such as Australia, New Zealand and UK, except that they are independent of the courts. Thus, this paper aims to discuss the nature and function of the division, its performance so far, and its future plan. It is hoped that by studying the strengths and weaknesses of the division, suggestions can be made to improve further its current structure and legal framework, for the betterment of single parent families in Malaysia.